Role of Interleukin 8 in Uterine Natural Killer Cell Regulation of Extravillous Trophoblast Cell Invasion - De Oliveira, L.G.; Lash, G.E.; Murray-Dunning, C.; Bulmer, J.N.; Innes, B.A.; Searle, R.F.; Sass, N.; Robson, S.C. (Placenta (Eastbourne), 2010)
Extravillous trophoblast cell (EVT) invasion of maternal tissues is critical for successful pregnancy. Decidual factors, including uterine natural killer (uNK) and T cell derived cytokines play a role in regulating this process. Interleukin (IL) 8 has been implicated as a regulator of EVT invasion. uNK cell stimulation of EVT invasion is associated with IL-8 levels. CD8+, total decidual and CD56 + uNK cells (8–10 and 12–14 weeks gestational age) were cultured. IL-8 mRNA and protein levels were determined. IL-8 receptors (IL-8RA and IL-8RB) were localised in first trimester placental bed biopsies. The effect of IL-8 ± IL-8 neutralising antibodies and CD8+ T cell or uNK cell supernatants ± IL-8 neutralising antibodies on EVT invasion was assessed. EVT secreted levels of MMP-2, MMP-9, uPA, PAI-1 and PAI-2 were assessed by substrate zymography or Western Blot. High levels of IL-8 protein and mRNA were detected in all samples. IL-8RA and IL-8RB were expressed by EVT. Exogenous IL-8 stimulated EVT invasion in a paracrine manner. uNK cell supernatants, but not CD8+ cell supernatants, stimulated EVT invasion. IL-8 neutralising antibody partially abrogated this uNK cell stimulated invasion. IL-8 increased levels of secreted MMP-2, but did not alter any of the other proteases or protease inhibitors tested. uNK cell stimulation of EVT invasion is partially mediated by IL-8. Unstimulated CD8+ T cells do not alter EVT invasion despite secreting similar levels of IL-8 as uNK cells.